PESANTREN, SEJARAH DAN METODE PEMBELAJARANNYA DI INDONESIA - Anik Faridah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2019)
AbstractPesantren is a traditional Islamic educational institution that grows and develops in the midst of Muslim society and is involved directly in efforts to educate the life of the nation and has contributed significantly to the implementation of education in Indonesia.Historically, the pattern of pesantren approach to the community through familiar and deeply rooted traditions has led pesantren to an education system that is full of flexibility and has a broad spectrum, beyond the boundaries of the pesantren itself. No exaggeration to say, pesantren is a deshooling society by making society as a learning society and make learning as a process that runs continuously.However, pesantren educational institutions are required to continue to innovate and able to read contextually the values of tradition that become inevitability to be earthed in the reality of pesantren education and demands wisdom. simplicity, independence, and sincerity need to be dedicated to the spirit of education in a contextual formulation that fits the ongoing development and changing lives. Thus simplicity will find its point in the development of efficiency and effectiveness of the institution, and independence will be directed to the formation of civil society, and sincerity will be concretized into the form of achievement development. Through it, pesantren and the surrounding community will be able to know their needs in real terms and will always develop themselves through tireless efforts to gain knowledge and knowledge as wide as possible.Â Keywords: pesantren, histories, and teaching method.